2015
DOI: 10.1097/prs.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors of Blood Transfusion in Abdominoplasty in Post–Bariatric Surgery Patients

Abstract: Risk, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…The present study showed that the majority of the patients consisted of women, as well as other studies [13][14][15][16][17][18] . Likewise, the mean age of 41 years was similar to that of other works [15][16][17]19 , but below the age of 44 years in an American work 14 and 48 years evidenced by other series 13,20 . The mean BMI before plastic surgery of 27.4kg/m 2 was similar to that found by other authors [13][14][15][16][17] , but well below the BMI of 35.6Kg/m 2 verified by Shermak et al 21 .…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study showed that the majority of the patients consisted of women, as well as other studies [13][14][15][16][17][18] . Likewise, the mean age of 41 years was similar to that of other works [15][16][17]19 , but below the age of 44 years in an American work 14 and 48 years evidenced by other series 13,20 . The mean BMI before plastic surgery of 27.4kg/m 2 was similar to that found by other authors [13][14][15][16][17] , but well below the BMI of 35.6Kg/m 2 verified by Shermak et al 21 .…”
Section: Introductionsupporting
confidence: 82%
“…As for the treatment of abdominal hernias during abdominoplasty, there was no need to use meshes. These hernias are more common when reductive gastroplasty is performed by open access 19 . In the present study, 57.5%…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding transfusions in abdominoplasties is limited with few recent studies representing rates as low as 0%–1.3% up to 26.6% in post-bariatric circular lipo-abdominoplasty (8, 9, 16, 20). Recently, a large cohort study of 20,310 post-bariatric abdominoplasties in the United States found transfusion rate of 9.3%, but less complex panniculectomies were also included (36). Our high rates may be partly due to the widely varying threshold of giving perioperative transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has its importance because, although considered generally safe, transfusions can cause immunological responses, including severe hemolytic reactions. Moreover, perioperative transfusions are associated with complications, higher mortality, longer hospitalization and cardiovascular events (36, 39).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to focus on body contouring procedures because of the relatively high risk and high sensitivity for hematomas in this patient population. 18 Furthermore, we aimed to evaluate the differences in complication occurrence, need for reoperation, and hospital length of stay for patients who received ketorolac perioperatively. We hypothesized that there would be no difference in morbidity between the groups after surgery.…”
mentioning
confidence: 99%